PEMIMPIN YANG MENDIDIK TANPA HENTI - Karel L. Mandagie (JURNAL MITRA MANAJEMEN, 2013)
Abstracts:Leaders is a decision maker to keep organization survive or sustain, coping with dynamicsenvironment from time to time. He should do the right decision. Leaders should teach anotherleaders as his successor, to keep the organization sustain. And Transformational leadershipultima-tely becomes moral in that it raises the level of human conduct and ethical aspiration ofboth leader and the led, and thus it has a transforming effect on both.”(Burns).